THE CONCEPT OF “THE HOLY SEED” AS A COPING STRATEGY IN EZRA-NEHEMIAH AND ITS IMPLICATIONS FOR SOUTH AFRICA - N S Cezula (Acta Theologica)
In a study describing the problems experienced by former political exiles who have returned to South Africa since 1990, Majodina argues that the psychological study of reintegration of refugees/exiles deserves a place in mainstream psychological research and not remain on the fringes. One of her basic assumptions is that coping plays a key mediating role in the reintegration process. Taking cue from her deliberation, this article aims to investigate the role played by psychological coping in the return of Judean exiles from Babylon in Ezra-Nehemiah. It examines these coping strategies in light of Tajfel’s and Turner’s theories of the Social Identity Approach (SIA) to give intelligibility to the ideologies that transpire. The article also presents Majodina’s Social Coping strategy to provide background for the discussion of implications for South Africa. The discussion culminates in the examination of implications of this discussion for South Africa. Where necessary, some South African neighbouring countries may be referred to, in order to illuminate the discussion.